The Response of Natural Esters when Being Under a Direct Current Electric Field for a Long Time - Kittisak Thungsook; René Manger; Markus H. Zink; Maja Kobus; Norasage Pattanadech (My University, 2024)
This study examines the dielectric behavior of natural esters exposed to a DC electric field over an extended period of time. The dielectric response was investigated by using polarization and depolarization current measurements. The natural ester sample was subjected to a DC electric field of 0.1 kV/mm, 0.5 kV/mm, 1 kV/mm, 1.5 kV/mm, and 2 kV/mm, respectively. Besides, the moisture content of natural esters was also controlled using a natural method. The test results showed that after being exposed to an electric field for an extended period of time of the natural ester, different forms of charge accumulation might be found partly depending on the initial condition of the investigated natural ester.
Keywords: Advanced Scientific Research Methods